A case of pulmonary artery sarcoma that was initially mis-diagnosed as pulmonary embolism. Issue 3 (29th March 2019) - Ushioda, Ryohei; Kitahara, Hiroto; Ise, Hayato; Koichi, Yuta; Wakabayashi, Naohiro; Tanaka, Chiharu; Nakanishi, Sentaro; Ishikawa, Natsuya; Kamiya, Hiroyuki
Abstract: Pulmonary artery sarcoma is a rare and highly malignant neoplasm. Early diagnosis and a multidisciplinary approach including surgical treatment and optimal medical therapy could prolong survival. Since the clinical symptoms and imaging findings of pulmonary artery sarcoma mimic pulmonary embolism, definitive diagnosis and surgical intervention are often delayed. In this report, a case of pulmonary artery sarcoma that was initially misdiagnosed as pulmonary embolism is presented.